Uncovering Viral Dose–Driven Control of Herpesvirus DNA Replication and Infection-Induced Nuclear Damage - Cegielski,Blazej (2025)
Herpes simplex virus type 1 (HSV-1) is a widespread DNA virus capable of establishing lifelong infections and eliciting diverse disease outcomes. The amount of virus that initially enters a cell, known as the multiplicity of infection (MOI), plays a critical role in shaping infection dynamics. However, its influence on virus–host interactions at the single-cell level remains to be fully elucidated. In this study, we explored how varying levels of viral input affect infection progression in individual human cells. Using fluorescent tagging and time-resolved imaging, we observed that higher viral input leads to more rapid viral activity and notable changes in the organisation of nuclear material. As the infection progresses, the structural arrangement within the nucleus becomes increasingly altered, eventually compromising nuclear integrity in a manner that depends on the level of viral exposure. Our observations suggest a dose-dependent relationship between viral input and nuclear architecture changes, with implications for how cells respond to and are impacted by infection. These findings underscore the significance of viral load in determining the cellular outcomes of HSV-1 infection and contribute to a better understanding of virus–host dynamics.